ANALISIS DAMPAK EKONOMI SISTEM PEMANTAUAN CERDAS PADA PRODUKSI KEDELAI - Marina, Ida; Sukmawati, Dety; Komariah, Ai (Journal of Sustainable Agribusiness, 2025)
This study analyzes the economic impact of implementing the SoySmart 360 intelligent monitoring system on soybean production through a field-based experimental approach. The system was tested on a 0.25-hectare experimental plot by comparing results between treatment plots equipped with smart monitoring technology and control plots managed conventionally. The findings indicate that the application of SoySmart 360 improved fertilizer and water-use efficiency by approximately 20%, reduced production costs, and increased soybean productivity by up to 25% compared to traditional farming practices. The system demonstrated an accuracy level of 92% in providing agronomic recommendations, confirming its reliability in supporting precise and data-driven decision-making. Economic analysis further revealed that input efficiency and improved yields contributed directly to higher farm income and strengthened the feasibility of soybean farming. Overall, the intelligent monitoring system delivers significant technical and economic benefits, positioning it as a strategic innovation to support national soybean production enhancement in the future.